Aortic bifurcation tear following blunt trauma in childhood - Shlomo Yellinek; Dimitri Gimelrich; Ofer Merin; Petachia Reissman; Marc Arkovitz (Elsevier, 2015)
Rupture of the abdominal aorta from blunt trauma is rare and aortic biforcation tear is extremely rare. We will present the management of a 2 year old boy who suffered blunt abdominal trauma and was operated in urgent fashion in our institution.